War songs and hope during the Second Chimurenga in Zimbabwe: a critical discourse analysis approach - Matiza, Vimbai M.; Mutasa, David (Routledge, 2022)
War songs played a pivotal role during the struggle for independence in Zimbabwe. War songs provoked people’s thoughts, feelings and mood to fight for the liberation of the country. Slogans, songs and music that were sung and performed during the war of liberation, popularly known as the Second Chimurenga (1971–1979), instilled hope in both the liberation fighters and the masses as they gave them the strength to continue fighting until the attainment of independence. The war songs that were inextricably linked to the hard-fought struggle were the bedrock or cornerstone in boosting the fighters’ morale. Thus, the aim of the article is to discuss the pivotal role of war songs in winning the struggle against colonialism through instilling hope in both the masses and fighters. The language embedded in war songs oozed with power and urged the African fighters to soldier on despite all odds. Using critical discourse analysis of six war songs, namely Maruza imi (You have been defeated), Rova ngoma Mutavara (Hit the drum, Mutavara), Nyika yedu yababa (Our country, the land of our forefathers), Mhoroi mose mose (Greetings everyone), Tichafara tasvika muZimbabwe (We will be happy when we get to Zimbabwe) and Mbuya Nehanda kufa vachitaura (Grandmother Nehanda died speaking), the article argues that war songs are embedded with messages and emotions that give participants the vigour and energy to succeed despite the odds.